Moral Values Found in Harry Potter and the Deathly Hallows Novel by J.K. Rowling - Juliani, Asarina Jehan; Tahrun, Tahrun; Yukamana, Hanni (Jurnal Pendidikan Tambusai, 2021)
This research aims to find out moral values in “Harry Potter and the Deathly Hallows” novel. The data of this research were obtained from words, phrases, sentences, and utterances. This research was using a qualitative descriptive method. There were three kinds of collecting the data, they were documentation, interview, and book review from another reader. Five major phases were used for the data analysis: they were data managing, reading, noting, classifying, interpreting, and representing. The results of data analysis shows that moral values in “Harry Potter and the Deathly Hallows” novel are commitment to something greater than oneself; self respect, but with humbleness or respect to others, self-discipline, and acceptance of personal responsibility; respect and caring for others; and caring for other living things and environment.